Factors Affecting Family Planning Service Delivery by Community Health Workers in District 2, Quezon City, Philippines: A Cross-Sectional Study - Nel Jason Ladiao Haw; Neil Eric Pecache; Niño Albiola; Karl Francis Chan; Ken Gerald Dela Cruz; Chloe Stephanie Gotianse; Sarah Stephanie Uy (Social Medicine Publication Group, 2016)
Background: In the Philippines, family planning (FP) service delivery is an integral part of the roles expected of community health workers who are at the forefront of primary health care delivery, especially among the underprivileged. District 2, Quezon City has the highest concentration of informal settlers in the country. Objective: To determine the factors that significantly affect FP service delivery by community health workers in District 2, Quezon City, Philippines Design: Cross-sectional study Setting: All community health workers in the 11 health centers in the District during the periods of April to September 2013 Measurements: The authors conducted primary quantitative and qualitative data collection on selected factors found in previous studies to be significantly correlated with contraceptive prevalence rate (CPR), the performance target measure for FP service delivery. Bivariate analysis and multiple regression were used to establish associations between the variables and CPR. Thematic clustering was used to extract themes and generate hypotheses for possible reasons on the strength of associations. Because the whole population of community health workers was sampled, confidence intervals and p-values were not reported and all associations were assumed to be significant. Results: Four factors reported moderate level of association with CPR: FP training received (r = 0.40), allowances received (r = 0.55), satisfaction with incentives (rs = 0.46), and age (r = -0.44). Multiple regression showed that these four variables account for 26% of the variation in CPR. For every unit increase in FP training (hours), allowance received (pesos), and rating higher in satisfaction with incentives, there is an increase of 2.85, 0.11, and 2.31 CPR percentage points, respectively. For every decrease in one year of age, there is an increase of 1.07 CPR percentage points. Limitations: Although the questionnaire was pretested and based on previous studies, data collection was prone to recall bias. There was no other available source of secondary data during the conduct of the study. The researchers informally confirmed some of the qualitative data from focus group discussions through interviews with supervisors and local leaders, and observation by the researchers themselves. Conclusions: The factors that have moderate impact on FP service delivery are FP training, allowances, satisfaction with incentives, and age. The authors recommend that the local health department increase training sessions, increase allowances and other benefits, and encourage younger people to be community health workers.